Anterior intermeniscal ligament: an anatomic study of its insertion pattern in Ghanaians - Ato Brown (Selcuk University, 2014)
The purpose of this study was to identify the various patterns of  attachment of the anterior intermeniscal ligament that is predominate in the Ghanaian as there is no known publication on this subject.The study was conducted in the Department of Anatomy of the School of Medical Sciences, University of Cape Coast and involved 42 paired cadaveric knees, from 16 males and 5 females. The incidence of the AIML was 40.5%.  The mean length of the AIML was 28.95mm; the mean width was 1.94mm, while the mean distance from mid-portion of the AIML to the insertion of the anterior cruciate ligament was 4.32mm. Type I pattern of attachment was the most common pattern of insertion observed (64.7%), followed by type II (29.4%) and then type III (5.9%). The incidence of the AIML may be lower in the Ghanaian populace than most reported studies.